2017
DOI: 10.1302/0301-620x.99b12.bjj-2017-0402.r2
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the ‘law of diminishing returns’ in magnetically controlled growing rods

Abstract: The 'law of diminishing returns' is also seen after serial distraction using MCGR. Compared to previously published data for CGRS, there is a gradual linear decline rather than a rapid initial decline in lengthening. In older, heavier children a reduced distraction ratio in the concave rod of the MCGR device is noted over time. Cite this article: 2017;99-B:1658-64.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 21 publications
4
40
0
Order By: Relevance
“…30 Thus, "law of temporary diminishing distraction gains" may be a more appropriate term to use for describing such reductions in MCGR lengthening observed here and in past studies. 11,12,24,25 The interesting feature of the "law of temporary diminishing distraction gains" is that it is a phenomenon unique only to the currently implanted rod under distraction. The gradual reductions of rod lengthening illustrated by increasing divergence between targeted and achieved length gains is only temporary.…”
Section: Discussionmentioning
confidence: 99%
“…30 Thus, "law of temporary diminishing distraction gains" may be a more appropriate term to use for describing such reductions in MCGR lengthening observed here and in past studies. 11,12,24,25 The interesting feature of the "law of temporary diminishing distraction gains" is that it is a phenomenon unique only to the currently implanted rod under distraction. The gradual reductions of rod lengthening illustrated by increasing divergence between targeted and achieved length gains is only temporary.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were distracted at 3-month intervals and had fluoroscopic images taken immediately after the distraction. There was also a significant decrease in T/I ratio which was a gradual linear decline over time [10].…”
Section: Discussionmentioning
confidence: 91%
“…44 Ahmad et al identified a near linear decrease in distraction over time. 42 Their analysis also demonstrated that after initial implantation of the MAGEC, there was no significant improvement in the coronal plane deformity during follow-up. The authors suggested that spinal distraction with MAGEC also follows the "law of diminishing returns".…”
Section: Magec In Cohort Studies: Clinical and Radiological Resultsmentioning
confidence: 98%
“…40,41 In a recent meta-analysis, there was no significant difference in the change in Cobb angle or incidence of complications between EOS patients treated by MAGEC or TGRs. 41 The variation reported in true distraction achieved compared to the desired distraction with MAGEC was investigated by Ahmad et al 42 Actual distraction with MAGEC had been reported between 33% and 45.5% of intended distraction. 37,43 For TGRs, increased spinal stiffness and spontaneous fusion over the duration of treatment can lead to the "law of diminishing returns" upon repeated lengthenings, whereby repeated lengthenings yield a decrease in the true distraction achieved.…”
Section: Magec In Cohort Studies: Clinical and Radiological Resultsmentioning
confidence: 99%